2022
DOI: 10.3390/ijms23052859
|View full text |Cite
|
Sign up to set email alerts
|

Leptin in Osteoarthritis and Rheumatoid Arthritis: Player or Bystander?

Abstract: White adipose tissue (WAT) is a specialized tissue whose main function is lipid synthesis and triglyceride storage. It is now considered as an active organ secreting a plethora of hormones and cytokines namely adipokines. Discovered in 1994, leptin has emerged as a key molecule with pleiotropic functions. It is primarily recognized for its role in regulating energy homeostasis and food intake. Currently, further evidence suggests its potent role in reproduction, glucose metabolism, hematopoiesis, and interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 125 publications
0
24
0
4
Order By: Relevance
“…Although leptin at 100 ng/ml failed to activate STAT 3, it could induce STAT 1α phosphorylation in the chondrocytes of obese patients ( Pallu et al, 2010 ). Leptin receptor activation initiated by leptin binding was reported to activate multiple signaling pathways including JAK/STAT ( Eldjoudi et al, 2022 ).…”
Section: Adipokine Signaling Pathways In Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Although leptin at 100 ng/ml failed to activate STAT 3, it could induce STAT 1α phosphorylation in the chondrocytes of obese patients ( Pallu et al, 2010 ). Leptin receptor activation initiated by leptin binding was reported to activate multiple signaling pathways including JAK/STAT ( Eldjoudi et al, 2022 ).…”
Section: Adipokine Signaling Pathways In Osteoarthritismentioning
confidence: 99%
“…It’s close association with OA have been widely reported in literature ( Collins et al, 2020 ). Clinical data has shown that there was a positive correlation between synovial adipokine level and OA activity index in elderly women with knee OA ( Eldjoudi et al, 2022 ; Ilia et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is an organokine that affects the activity of bone morphogenetic proteins (BMPs) and is an inhibitor of the Wnt/β-catenin metabolic pathway in bone cells. Although sclerostin is as an osteocyte-specific protein, recent studies have shown that several additional cell types express SOST and can produce the sclerostin protein, such as osteoclasts, chondrocytes, and in tissues such as the kidney, heart, and liver [ 73 , 84 , 85 , 86 ].…”
Section: General Aspects Of Ra and The Role Of Myokines Osteokines Ad...mentioning
confidence: 99%
“…Inhibiting the Wnt pathway by SOST involves activating caspases and pro-inflammatory cytokines produced by the synovial membrane, increasing bone resorption, and stimulating soluble antagonists of the canonical Wnt/βcatenin signaling pathway with subsequent inhibition of proliferation, maturation, and differentiation of osteoblast progenitors. Sclerostin can also antagonize BMP signaling directly by inhibiting BMP-7 secretion, leading to intracellular retention and proteasomal degradation of BMP-7, and blocking BMP signaling selectively in osteocytes that simultaneously synthesize sclerostin and BMP-7 proteins [ 73 , 75 , 84 , 85 , 86 ].…”
Section: General Aspects Of Ra and The Role Of Myokines Osteokines Ad...mentioning
confidence: 99%
See 1 more Smart Citation